2021
DOI: 10.21608/jpp.2021.154325
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of White Maize Inbred Lines Via Line X Tester Analysis

Abstract: Combining ability analysis was conducted using line x tester design for seven inbred lines of maize which were crossed to three single crosses as testers at Ismailia Agricultural Research Station during 2016 growing season. In 2017 season, 21 crosses in addition to one check hybrid were evaluated at three locations. Highly significant differences were found between the locations for all studied traits. Mean squares due to crosses, their partitions and their interaction with locations were significant or highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 6 publications
24
7
0
Order By: Relevance
“…The combined analysis of variance showed highly significant mean squares due to locations (Loc) for all the studied traits (Table 2), indicating the presence of a clear variation between the two locations in climatic and soil conditions for these traits. These results agreed with those reported by El Hosary et al (2018), Gamea et al (2018), El-Shahed et al (2021) and Mousa et al (2021).…”
Section: Analysis Of Variancesupporting
confidence: 93%
See 3 more Smart Citations
“…The combined analysis of variance showed highly significant mean squares due to locations (Loc) for all the studied traits (Table 2), indicating the presence of a clear variation between the two locations in climatic and soil conditions for these traits. These results agreed with those reported by El Hosary et al (2018), Gamea et al (2018), El-Shahed et al (2021) and Mousa et al (2021).…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…This finding showed that nonadditive type of gene action was more affected by locations than the additive ones. These results are in agreement with the findings of Ibrahim et al (2010), Abd Allah et al (2011, Mousa and Aly (2012), Abdel-Moneam et al (2014) and Mousa et al (2021). They found that the non-additive genetic effects were more sensitive to environmental changes than the additive genetic effects.…”
Section: Variance Componentssupporting
confidence: 93%
See 2 more Smart Citations
“…The significant GCA implies that breeders can exploit the available genetic variability in the identification of elite materials with desirable traits, whereas significant SCA effects suggest that promising single cross combinations may be found. However, each of Mosa (2010), Mostafa (2018) and Mousa et al (2021) reported that the tested genotypes should exhibit enough genetic diversity for an effective breeding program via. Top cross modeling.…”
Section: Introductionmentioning
confidence: 99%